Pemanfaatan AI Menggunakan ChatGPT Untuk Meningkatkan Kinerja Anggota Fatayat NU PC Tangerang - Frisma Handayanna; Maryanah Safitri; Tri Santoso; Albert Riyandi (CV. Multi Kreasi Media, 2024)
AI developers are currently working to ensure that the technology is used responsibly and benefits all parties. Collaboration between different fields and stakeholders is essential to create a just and sustainable AI future. The transformation of AI from a theoretical concept to a practical technology that impacts everyday life is an amazing journey. Like Fatayat NU. This organization faces several problems in implementing their activities. The problems that organizations often face can be very diverse, and usually involve various operational, strategic, and human aspects. Here are some of the problems faced: 1) Ineffective communication where information does not reach team members clearly, causing confusion or errors. 2) Lack of coordination between teams where different teams do not collaborate well, causing delays and low efficiency. 3) Difficulty in decision making where decisions are slow or less accurate due to lack of information or analysis. 4) Challenges in recruitment where the recruitment process is long and complicated, or difficulty finding the right candidate. This community service activity aims to improve the ability of female members of Fatayat NU PC Kota Tangerang in using the ChatGPT application and develop their knowledge and skills. The same goal is also to obtain publication in editorial media of journals that are not yet accredited or that have been accredited.